Evaluating Cost Performance and Unit Rate Optimization in Surface Maintenance Operation (SMO) Earthwork Service Contracts - Alexander Alexander; Darmawan Pontan; Efa Ayu Nabila; Lunatari Sanbella (Pandawan Sejahtera Indonesia, 2025)
The Surface Maintenance Operation (SMO) Construction Services Work Unit Rate Earthwork (WUR EW) project in the Rokan Block, Indonesia, utilizes a unit price contract model with hypothetical volumes. This contractual model transfers the risk of uncertain work quantities from the project owner to the contractor. This study aims to analyze the characteristics of this contract and formulate a secure strategy for preparing bidding prices and managing construction costs. The research employed a quantitative analysis of historical data from two work packages (Package 3 and Mitigation Package 3). The analysis was conducted through the calculation of Key Performance Indicators (KPIs) such as the Cost Performance Index (CPI) and Budget Variance (BV), as well as Cost and Quantity Variance Analysis per work item. The results indicate that both projects achieved excellent cost performance, exceeding the planned profit targets (Realized CPI > Planned CPI). The most effective strategy was to set a high profit percentage on the top 10 Earthwork & Civil items (the Pareto items), which experienced significant volume increases and were the main drivers of the total profit growth.